2021
DOI: 10.1155/2021/4084566
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Ameliorates HFD-Induced NAFLD through Regulation of the AMPK and NLRP3 Inflammasome Signal Pathways

Abstract: Nonalcoholic fatty liver disease (NAFLD) is closely related to glycolipid metabolism and liver inflammation. And there is no effective drug approved for its clinical therapy. In this study, we focused on mangiferin (Man) and explored its effects and mechanisms on NAFLD treatment based on the regulation of glycolipid metabolism and anti-inflammatory in vivo and in vitro. The results exhibited that Man can significantly attenuate liver injury, insulin resistance, and glucose tolerance in high-fat diet- (HFD-) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Combined with the results of the current study, it is hypothesized that metformin inhibits lipid accumulation by decreasing induction of ferroptosis in ox-LDL-stimulated macrophages. The AMPK signaling pathway is a major intracellular energy metabolism pathway, which serves a protective effect on atherosclerosis by inhibiting inflammation, regulating lipid metabolism, antioxidant activity, as well as suppressing immune responses (39)(40)(41). In addition, The ERK/MAPK signaling pathway serves an important role in the process of atherosclerosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the results of the current study, it is hypothesized that metformin inhibits lipid accumulation by decreasing induction of ferroptosis in ox-LDL-stimulated macrophages. The AMPK signaling pathway is a major intracellular energy metabolism pathway, which serves a protective effect on atherosclerosis by inhibiting inflammation, regulating lipid metabolism, antioxidant activity, as well as suppressing immune responses (39)(40)(41). In addition, The ERK/MAPK signaling pathway serves an important role in the process of atherosclerosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation in the liver is beneficial for glucose consumption, lipid oxidative decomposition, and body energy provision. Many AMPK agonists, such as mangiferin ( Yong, Ruiqi et al, 2021 ), berberine ( Zhu, Bian et al, 2019 ), and metformin ( Zamani-Garmsiri, Hashemnia et al, 2021 ), are considered potential drugs for MAFLD treatment. The results of this study are the first to demonstrate that Nok can improve MAFLD based on activation of hepatic AMPK in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted, and quality was assessed by integrity. Relevant sample processing, sequencing, and data analysis methods were described in our previous research ( Yong, Ruiqi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study indicated that body weight, liver weight, TC, TG, ALT, and AST were reduced after treatment with Man, while NLRP3, caspase-1, IL-1β, and GSDMD expression were downregulated in vivo and in vitro . These results indicated that the anti-NAFLD activity of Man is mediated by its anti-inflammatory effects via NLRP3 inflammasome inhibition ( Yong, Ruiqi et al, 2021 ).…”
Section: Plant-derived Active Ingredients Treat Nafld By Regulating N...mentioning
confidence: 96%